2019
DOI: 10.3390/ijerph16162857
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity, Behavior, and Lethal Effects of Cadmium, Microplastics, and Their Mixtures on Pomatoschistus microps Juveniles from Two Wild Populations Exposed under Laboratory Conditions―Implications to Environmental and Human Risk Assessment

Abstract: Microplastics (MPs) were found to modulate the toxicity of other pollutants but the knowledge on the topic is still limited. The goals of this study were to investigate the short-term toxicity of cadmium (Cd) to wild Pomatochistus microps juveniles, the potential modulation of acute Cd toxicity by 1–5 µm polyethylene MPs in this species, and possible differences of sensitivity to Cd and MPs-Cd mixtures between juveniles from two distinct wild populations. Juveniles were collected in the estuaries of Minho (M-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(37 citation statements)
references
References 114 publications
1
35
1
Order By: Relevance
“…In line with MPs/NPs activity as carriers or vectors of environmental contaminants, studies using fish cell lines have revealed that, while pristine plastics show no toxicity, those sampled from different islands around the world do [96], and so do those that have been mixed with human pharmaceuticals [97]. MPs/NPs were shown to modulate the toxicities a range of pollutants/toxicants, including phenanthrene [75], mercury [49], cadmium [46][47][48], polychlorinated biphenyls (PCBs) [98], gold ions [99], and the antibiotic roxithromycin [100], in fishes. However, adsorption of toxicants by the plastics could also potentially lower their toxicity, and such is the case for a complex mixture of polycyclic aromatic hydrocarbons (PAHs) [101].…”
Section: Toxicity Of Mps/nps In Fishesmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with MPs/NPs activity as carriers or vectors of environmental contaminants, studies using fish cell lines have revealed that, while pristine plastics show no toxicity, those sampled from different islands around the world do [96], and so do those that have been mixed with human pharmaceuticals [97]. MPs/NPs were shown to modulate the toxicities a range of pollutants/toxicants, including phenanthrene [75], mercury [49], cadmium [46][47][48], polychlorinated biphenyls (PCBs) [98], gold ions [99], and the antibiotic roxithromycin [100], in fishes. However, adsorption of toxicants by the plastics could also potentially lower their toxicity, and such is the case for a complex mixture of polycyclic aromatic hydrocarbons (PAHs) [101].…”
Section: Toxicity Of Mps/nps In Fishesmentioning
confidence: 99%
“…On the other hand, organic pollutants could be adsorbed onto MPs/NPs [37][38][39][40][41] and there is evidence that this could potentially enhance their effective uptake and toxicity [42][43][44][45]. Likewise, MPs/NPs are known to interact with metallic toxicants such as Cadmium [46][47][48], Mercury [49], and other toxic trace elements [50], and could potentially serve as vectors for pollutant transfer to living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies revealed lower toxicity or no effect of metal and MP co-exposure. Thus, MPs did not influence the uptake and toxicity of silver (Ag) in zebrafish [61] while an antagonistic interaction with cadmium (Cd) was observed in the common goby juveniles [62]. In this regard, the ability of contaminants to be adsorbed to plastics may depend on the plastic's features and the type of contaminant [63], which directly influences its combined toxicity.…”
Section: The Presence Of Nanoplastics Increases the Toxicity Of Metalsmentioning
confidence: 99%
“…In juvenile brown trout, also no effect of PS MP on oxidative stress was found [86]. Furthermore, in common gobies (Pomatoschistus microps) the LPO level was not affected by PE MP exposure in several studies [33,[87][88][89]. Nevertheless, other studies showed that some MP may induce oxidative stress in fish [19,90,91].…”
Section: Effects Of Mpmentioning
confidence: 97%